Pengaruh Suhu dan Waktu Pemanasan Terhadap Kualitas Interior Telur Ayam Hasil Persilangan Ayam Kedu Dan Bangkok - Nining Haryuni; Farid Abdullah; Anna Lidyawati; - Lestariningsih (Journal of Science Nusantara, 2022)
The purpose of this study was to determine the effect of temperature and duration of heating on the interior quality of chicken eggs from crosses between Kedu chickens and Bangkok chickens. This research is a biological research using a 2x4 factorial Completely Randomized Design (CRD). The first factor is temperature (P) (27 and 32 0C) and the second factor is heating time (T) (0, 6 and 12 hours) where each treatment uses 5 chicken eggs. The results of statistical analysis showed that temperature had no significant effect (P>0.05) on egg weight loss, egg yolk index and egg white height. The heating time had a very significant effect (p<0.01) on the yolk index and egg white height but had no significant effect (p>0.05) on egg weight loss. The interaction between the two treatment factors gave no significant effect (p>0.05) on egg weight loss and egg yolk index but gave a very significant effect (p<0.01) on egg white height. Egg weight loss in this study ranged from 0.46 -0.50%; Egg yolk index ranged from 0.32-0.39 and egg white height ranged from 5.35-7.45mm. The conclusion of this study is that the temperature and duration of the heating process can reduce the interior quality of chicken eggs from a cross between a Kedu chicken and a Bangkok chicken